2006
DOI: 10.1127/0935-1221/2006/0018-0361
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of lead uptake on the microstructure of a (Mg, Ca)-bearing bentonite (Prrenjas, Albania)

Abstract: The article addresses Pb uptake and microstructural/morphological modifications of a (Mg, Ca) bentonite (Prrenjas, Albania) after interaction with solutions of elevated lead content. Comparison is made with a Wyoming montmorillonite transformed to the Mg-dominated form. Characterized by X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) the Prrenjas bentonite is predominantly a smectite, containing 10% of interlayered illite, with associated kaolinite, antigorite, halloysite and minor chlorite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…80 For a given clay composition at relatively low H2O activities, hydration of the charge-balancing counter ions is the dominant interaction leading to swelling, and differences in swelling behavior are directly related to the differences in the cation hydration energy. [75][76][77]81 Previous experimental studies of hectorite swelling and its interactions with cations and water molecules have used a variety of techniques, including X-ray diffraction (XRD), 46,[82][83][84][85][86][87][88][89][90][91] thermogravimetric analysis (TGA), 40,46,91 quasi-elastic neutron scattering (QENS), 57,58,60,64,65,67 and NMR spectroscopy. 39,40,42,[44][45][46] XRD is widely used and provides information about the 6 effects of, for instance, relative humidity on the interlayer spacing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 For a given clay composition at relatively low H2O activities, hydration of the charge-balancing counter ions is the dominant interaction leading to swelling, and differences in swelling behavior are directly related to the differences in the cation hydration energy. [75][76][77]81 Previous experimental studies of hectorite swelling and its interactions with cations and water molecules have used a variety of techniques, including X-ray diffraction (XRD), 46,[82][83][84][85][86][87][88][89][90][91] thermogravimetric analysis (TGA), 40,46,91 quasi-elastic neutron scattering (QENS), 57,58,60,64,65,67 and NMR spectroscopy. 39,40,42,[44][45][46] XRD is widely used and provides information about the 6 effects of, for instance, relative humidity on the interlayer spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies of hectorite swelling and its interactions with cations and water molecules have used a variety of techniques, including X-ray diffraction (XRD), , thermogravimetric analysis (TGA), ,, quasi-elastic neutron scattering (QENS), ,,,,, and NMR spectroscopy. ,,, XRD is widely used and provides information about the effects of relative humidity on the interlayer spacing, for example. ,,, Due to static and dynamic disorder in the interlayer, XRD typically does not provide the specific atomic positions needed for detailed structural analyses, particularly with respect to the hydrogen positions, and provides essentially no information about dynamics. Neutron scattering also probes interlayer structure and H 2 O diffusion and has been recently used to study interlayer water diffusion in smectites. ,,,,, Diffusion of water in one- and two-layer hydrates of hectorite is typically 10 and 3–6 times slower than in bulk water, respectively. ,,,,, Unfortunately, neutron scattering techniques have difficulty distinguishing between the H atoms of interlayer H 2 O molecules and those of structural OH – groups, and structural OH – groups contribute background signal and complicate data analysis. ,, Thus, QENS has been used to investigate water diffusion in the interlayer galleries of hectorite for only fluorhectorites, in which F – substitutes fully for structural OH – , ,,,,, whereas natural hectorites often contain nearly equal mixtures of structural OH – and F – .…”
Section: Introductionmentioning
confidence: 99%
“…At high ionic strength, Pb adsorption is pHdependent, suggesting inner sphere complexation where adsorption occurs on functional groups existing on the montmorillonite edges. TEM observations showed that Pbexchanged on a natural bentonite surface displayed microaggregates or microstructure units, consisting largely of an association of small particles packed together without interparticle pore space (Jozja et al 2006).…”
Section: Millions Of Yearsmentioning
confidence: 99%